The Legacy of the Great War : Ninety Years On - Winter, J. M. (Book collections on Project MUSE., 2009)
In late 2007 and early 2008, world-renowned historians gathered in Kansas City for a series of public forums on World War I. Each of the five events focused on a particular topic and featured spirited dialog between its prominent participants. The forums addressed topics about the Great War that have long fascinated both scholars and the educated public: the origins of the war and the question of who was responsible for the escalation of the July Crisis. From the perspectives of a German and a British scholar discussion ensued on the nature of generalship and military command and also the private soldiers' experiences of combat, revealing their strategies of survival and negotiation. These discussions show that the Great War was 'great' not merely because of its magnitude, but also because of its revolutionary effects.